CURRENT SITUATION OF JOB BURNOUT AND LEADERSHIP STYLES IN MANUFACTURING COMPANY MANAGERS IN CORTÉS, HONDURAS - Padilla-Sánchez, Gissel; Rodríguez-Gallardo, Kelly; Salinas-Morales, Jennifer (LACCEI, 2025)
The objective of this research was to compare the level of job burnout of the leaders of manufacturing companies in Cortes, Honduras according to their personality style. Therefore, it was carried out using a quantitative approach with a descriptive-correlational scope, a non-experimental-cross-sectional design, applying a survey to which two instruments were integrated: Maslach’s Burnout Inventory and the DISC test of leadership styles. According to the results, it was shown that Burnout syndrome affects managerial profiles presenting a medium level in characteristics and symptomatology (54% of the sample) and 38% present a high level, proving to be a health risk. As for the leadership profile according to the DISC dimensions, managers showed on average greater characteristics linked to the dominant and controlling style; on the other hand, the style of strength and influence reflect a lower level in the behaviors expressed. When assessing the relationships between Burnout and leadership styles, it was shown that the dimensions of the dominant and solid personality show a statistically significant association with the prevalence of job burnout (r=0.628 and r=-0.432 respectively). This reflects that managers whose behavioral characteristics are linked to a greater need to direct, control, take risks and less need to serve, being optimistic, calm and patient will be more likely to manifest symptoms linked to Burnout.